The Prognostic Significance of Low-Frequency Somatic Mutations in Metastatic Cutaneous Melanoma - Zhao, Xiaobei; Little, Paul; Hoyle, Alan P.; Pegna, Guillaume J.; Hayward, Michele C.; Ivanova, Anastasia; Parker, Joel S.; Marron, David L.; Soloway, Matthew G.; Jo, Heejoon; Salazar, Ashley H.; Papakonstantinou, Michael P.; et al. (Frontiers in Oncology, 2019)
BACKGROUND: Little is known about the prognostic significance of somatically mutated genes in metastatic melanoma (MM). We have employed a combined clinical and bioinformatics approach on tumor samples from cutaneous melanoma (SKCM) as part of The Cancer Genome Atlas project (TCGA) to identify mutated genes with potential clinical relevance. METHODS: After limiting our DNA sequencing analysis to MM samples (n=356) and to CANCER CENSUS gene list, we filtered out mutations with low functional significance (snpEFF). We performed Cox analysis on 53 genes that were mutated in 3% of samples and had 50% difference in incidence of mutations in deceased subjects versus alive subjects. RESULTS: Four genes were potentially prognostic [RAC1, FGFR1, CARD11, CIITA; false discovery rate (FDR) <0.2]. We identified 18 additional genes (e.g. SPEN, PDGFRB, GNAS, MAP2K1, EGFR, TSC2) with less confidence for being prognostic (FDR <0.4). Most somatic mutations in these 22 genes were infrequent (<10%), associated with high somatic mutation burden, and evenly distributed across all exons, except RAC1 and MAP2K1. Mutations in only 9 of these 22 genes were also identified by RNA sequencing in >75% of the samples that exhibited corresponding DNA mutations. The low frequency, UV signature type, and RNA expression of the 22 genes in MM samples was confirmed in a separate multi-institution validation cohort (n=413). An underpowered analysis within a subset of this validation cohort with available patient follow-up (n=224) showed that somatic mutations in SPEN and RAC1 reached borderline prognostic significance [log-rank favorable (p=0.09) and adverse (p=0.07), respectively]. We conclude that expressed somatic mutations in infrequently mutated genes other than the well-characterized ones (e.g. BRAF, RAS, CDKN2A, PTEN, TP53) may have some prognostic significance in MM.